THE PERIOPERATIVE NURSE’S ROLE IN PATIENT-FOCUSED FUNDING - Thain, Leanne (Operating Room Nurses Association of Canada Journal, 2012)
All provinces across Canada are currently struggling with long surgery wait times. British Columbia (BC) has recently implemented an improvement strategy called Patient Focused Funding (PFF) whereby health authorities are offered additional money for completing extra surgeries. System wide change, when made without engagement by all involved parties, rarely achieves expected outcomes suggesting PFF would benefit from the participation of the entire operating room (OR) team. Perioperative nurses, in the role of patient advocate, are well suited to observe and report patient focused outcomes thereby limiting the unintended and negative consequences associated with proposed changes. This article seeks to inform Canadian perioperative nurses about PFF and explain why it is important for nurses to participate. At the time of writing, Ontario and Alberta had also announced plans to implement some form of PFF. It is anticipated that, if proven successful, BC’s experience will likely be duplicated in other provinces.